Contemporary mosque architecture in Turkey - Moustafa, Samaa (AUC Knowledge Fountain, 2013)
Early in the twentieth century in a quest for national identity and a need for modernity - both are products of the west - Turkey among many other Islamic countries embarked on a massive building project as part of its broader process of modernization. While new forms and styles were incorporated to mirror the modern and civilized vision of the new nation-state, the architecture of the mosque remained condservative with a few exceptions which started to appear only in the last quarter of the same century. The architecture of the medieval mosque has enriched our minds with knowledge about Islamic religious values, social cultures, local traditions and craftsmanship. Today, the architecture of the contemporay mosque confronts us with stiring debates between binary opposing perspectives such as modernity versus tradition, nationalism versus religion and state versus society. As a case study Turkey has a strong history of nationalism. Its westernization began in the eighteenth and nineteenth centuries and its modernization in the first half of the twentieth century. There have been two national revivals in its architectural culture. It is perhaps Turkey more than any other country that can shed light on how secularization brought about a profound effect on the role of religion and the mosque as evident from the ongoing controversis regarding the design, the location and even the number of mosques. Other than religion, social and architectural cultures are other important areas where change and transformation as the impact of modernization is greatly manifested. The new architecture and city planning changed the built environment; the mosque as one of its many other elements was affected by the change. Furthermore new institutions emerged and took over the social and educational role of the mosque and its place in public social life. Were all these changes expressed in the architecture of modern mosques? What kind of appraoch has been taken in the design of modern mosques? What is the role that the strong Ottoman architectural tradition came to play in the architecture of modern mosques? What kind of religious, social and political implications do the new examples yield? Have the new examples expressed the spirit of Islam since the mosque's primary function is a place of worship? Equally important have they expressed the spirit of the time? It is within the inseparable political, social and cultural contexts that this research seeks to study and analysis the architecture of the modern mosque - "the most Islamic building par excellence" - in Turkey.